A case of KAT6A syndrome with a newly discovered mutation in the KAT6A gene, mainly manifested as bone marrow failure syndrome. Issue 1 (31st December 2023) - Ai, Qi; Jiang, Lihua; Chen, Yun; Yao, Xiuyun; Yin, Jing; Chen, Sen
ABSTRACT: Objective: The clinical and genetic characteristics of a child with inherited bone marrow failure syndrome as prominent clinical manifestations and special facial features were analyzed, and the etiology and mechanism were explored in, combination with clinical practice. Methods: Blood samples and clinical information were collected separately from the proband and their biological parents. The pathogenic variant was verified using next-generation sequencing technology screening, and the candidate variable sites were confirmed by using Sanger sequencing among all members of the family. Results: A heterozygous nonsense mutation in exon 17 of KAT6A (NM_006766), c.4177G > T (p.E1393*) predicted to cause truncation within the acidic domain of the protein was identified. Pedigree analysis did not reveal any variation in this locus between the proband's father and mother. No report of this pathogenic variant was found in a literature search of domestic and foreign databases, indicating that it is a newly discovered mutation. According to the guidelines of the American College of Medical Genetics, the variation was preliminarily determined to be a pathogenic. The newly discovered heterozygous mutation in KAT6A may be the cause of the disease in this child. Additionally, inherited bone marrow failure syndrome is a prominent manifestation. Conclusion: This study not only provides us with an in-depth understanding of this rare syndrome but also deepens our understanding of the function of KAT6A .